In the snow - Poulton, Mike; Brychta, Alex Stewart, Sarah-Jane Storr, Duncan (Oxford University Press, 1988)
In the Snow is a charming children's story that takes place during a snowy winter day. The story follows a young protagonist who ventures outside to explore the magical, snow-covered world. As they journey through the winter wonderland, they encounter various adventures, from building snowmen to sledding and making snow angels. Along the way, the protagonist meets friends and animals, learning important lessons about nature, friendship, and the joy of simple pleasures. The story emphasizes the beauty of winter, the excitement of outdoor play, and the warmth of companionship during the colder months.